Nares Strait and the petroleum explorer - McMillan, Neil J. (Meddelelser om Grønland. Geoscience, 1982)
It is important to be able to make intelligent guesses concerning the effect of lateral movement along Nares Strait on the resulting sedimentary section and the heat regime. A prognosis of the theoretical well - Lincoln No. 1 - would need to contain forecasts concerning the conditions of hydrocarbon generation in the sediments. Case No. 1 for the postulated sedimentary section assumes 250 km of left-lateral movement along the Nares Strait lineament. Rocks are Lower Cretaceous to Pleistocene. Attendant heat is assumed to be high. Case No. 2 assumes very little movement along the lineament and, therefore, a relatively quiet tectonic history. Rocks are Cambrian to Pleistocene. Attendant heat is assumed to be average. A simulated analysis of the geochemistry of the situation in Case No. I reveals that maximum expulsion of hydrocarbons occurs at 4000 metres' depth. In Case No. 2 the maximum expulsion would occur at 5000 metres. Therefore, it is tentatively concluded that Case No. I would provide the best conditions for hydrocarbon generation and entrapment at approximately 1000 metres shallower than Case No. 2. Large-scale movement along the Nares Strait lineament and the attendant higher heat regime would be a beneficial circumstance for the petroleum explorer.